2007
DOI: 10.1111/j.1475-097x.2007.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of isokinetic strength imbalance ratios measured using the Cybex NORM dynamometer

Abstract: The main aim of this study was to examine the absolute and relative reliability of some commonly used strength imbalance indices such as concentric hamstring-to-concentric quadriceps ratio, eccentric hamstring-to-concentric quadriceps ratio and bilateral concentric and eccentric strength ratios. An additional aim was to examine the reliability of the peak torque and work of the knee extensor and flexor muscles measured using the Cybex NORM dynamometer. Eighteen physically active healthy subjects (mean +/- stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
158
11
12

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(204 citation statements)
references
References 46 publications
19
158
11
12
Order By: Relevance
“…3,6,19 However, there is still a lack of consensus on what a normal imbalance is and how much deviation is acceptable. 20 The current findings indicate that strength training can decrease lower body muscle imbalances, agreeing with the available previous research. Golik-Peric and colleagues found that 4 weeks of isoinertial and isokinetic training in athletes improved ipsilateral muscle symmetry by increasing the concentric hamstring to quadriceps torque ratio (conH/Q).…”
Section: Discussionsupporting
confidence: 81%
“…3,6,19 However, there is still a lack of consensus on what a normal imbalance is and how much deviation is acceptable. 20 The current findings indicate that strength training can decrease lower body muscle imbalances, agreeing with the available previous research. Golik-Peric and colleagues found that 4 weeks of isoinertial and isokinetic training in athletes improved ipsilateral muscle symmetry by increasing the concentric hamstring to quadriceps torque ratio (conH/Q).…”
Section: Discussionsupporting
confidence: 81%
“…the data of our study were smaller than the results found with athletes from other sports (soccer, track and field, basket, fencing, and alpine skiing; N=41) where a percentage asymmetry ((stronger-weaker)/ stronger x 100%) of 108.6% was found for the stronger leg during testing of maximum isometric contractions in the closed chain (9). for elite soccer players tested in the leg-press (technogym, Italy), also a greater asymmetry of maximum strength (1 rM) between the legs was found.…”
Section: Discussioncontrasting
confidence: 55%
“…from 41 sports athletes (soccer, track and field, basket, fencing, and alpine skiing) the peak force unfolded during the closed-chain maximum isometric contractions, measured using a load cell with a knee angle about 100°. the asymmetry index ((stronger -weaker)/stronger x 100%) was 108.6% for the stronger leg (9). In another study the lower-limb asymmetrical strength differences of soccer players (40 males, 26 females, national collegiate athletic association Division I) showed a significant greater peak force scaled for 2/3 body mass with the right leg versus left leg during isometric mid-thigh pulls (p < 0.05) (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the objective is to measure strength asymmetries, the intraclass correlation coefficients reliability appears to be low to moderate (Impellizzeri et al, 2008).…”
Section: Muscular Strength Isokinetic Testsmentioning
confidence: 99%